2022
DOI: 10.15829/1560-4071-2022-4810
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, morphological and molecular biological examination of the myocardium in COVID-19 patients

Abstract: The presence of coronavirus-associated myocarditis remains controversial despite elevations in cardiac troponin and natriuretic peptide in many patients.Aim. To assess the morphological changes in the myocardium of patients who died due to coronavirus disease 2019 (COVID-19) and compare them with the intravital level of cardiac biomarkers.Material and methods. A total of 420 hospital charts and 77 autopsies of those who died from COVID-19 were analyzed. In 15 of 77 cases (19%) with histologically suspected myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…At the same time, no significant association was found between inflammatory markers and morphologically by confirmed myocarditis, and no convincing evidence was obtained on the direct involvement of the SARS-CoV-2 virus in the induction of myocarditis. This fact once again confirms the theory of the pathogenesis of a severe course of COVID-19, based on predominantly immune damage to the vascular endothelium and the formation of microthrombosis [ 48 ].…”
Section: Pathogenesis Of Myocardial Damage Against the Background Of ...supporting
confidence: 84%
See 1 more Smart Citation
“…At the same time, no significant association was found between inflammatory markers and morphologically by confirmed myocarditis, and no convincing evidence was obtained on the direct involvement of the SARS-CoV-2 virus in the induction of myocarditis. This fact once again confirms the theory of the pathogenesis of a severe course of COVID-19, based on predominantly immune damage to the vascular endothelium and the formation of microthrombosis [ 48 ].…”
Section: Pathogenesis Of Myocardial Damage Against the Background Of ...supporting
confidence: 84%
“…There was myocardial damage in the range of 13–41% in hospitalized adult patients with COVID-19 which causes high mortality from cardiovascular complications [ 48 ]. However, current data on the tropism of SARS-CoV-2 to the myocardium is different.…”
Section: Pathogenesis Of Myocardial Damage Against the Background Of ...mentioning
confidence: 99%
“…These changes are associated with the repair of the consequences of cytokine imbalance and angiopathy in the acute phase of coronavirus infection, which leads to post-acute sequelae of SARS-CoV-2 infection (PASC), as evidenced by the decrease in the expression level of endothelial activation markers such as VEGF, VWF, Ang1, and C1q. In our previous study, we showed that the expression levels of these markers increase in the acute phase of coronavirus infection [ 28 ]. This is consistent with the literature data that myocardial damage in the acute phase of the coronavirus infection is due to systemic manifestations of cytokine storm and generalized angiopathy [ 19 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, повреждение эндотелия может привлекать моноциты, активирующие путь комплемента и вызывающие апоптотическое повреждение кардиомиоцитов, инициированное макрофагами [15]. В предыдущих исследованиях мы показали, что основными морфологическими изменениями в остром периоде COVID-19 является эндотелиит и его осложнения в виде тромбозов и кровоизлияний [16,17]. А в ряде исследований наряду с ангиопатией острого периода показано значимое увеличение CD68 + -макрофагов в ткани миокарда в остром периоде COVID-19 [15,18].…”
Section: Discussionunclassified